Stability Analysis of Traveling Waves to Advection-Diffusion Equation Involving Square-root - Mohammad Ghani; Wahyuni Ningsih; Nailul Izzati (LPPM Institut Teknologi Sepuluh Nopember, 2022)
In this paper, we study the existence and stability of advection-diffusion equation involving square-root. We first change the original equation into the traveling wave by using ansatz transformation. Then, we apply the appropriate perturbation to establish the energy estimate under small perturbation and large wave amplitude. These results of energy estimates are used to prove the stability of traveling wave solutions.